Effect of silicone resin as precursor and binder on the properties of alumina-based ceramic cores using ball-shaped powders. Issue 2 (1st February 2019) - Yang, Zhigang; Zhao, Zhijia; Yu, Jianbo; Ren, Zhongming; Ma, Shiqing; Wang, Zhi
Abstract: Al2 O3 -based ceramic cores with uniform microstructure were fabricated by sintering ball-shaped Al2 O3 powders as the matrix and silicone resin as the precursor and binder in air atmosphere. Effects of silicone resin content and sintering temperature on phase composition, microstructure and properties of the Al2 O3 -based ceramic cores were investigated. Results showed that a low sintering rate was beneficial for preparing high-quality Al2 O3 -based ceramic cores with no defects and cracks. Silicone resin was uniformly adhered on the surface of the ball-shaped Al2 O3 particles, playing a well role in connecting Al2 O3 particles. Sintering process made the organic-inorganic transformation process of silicone resin happen, leading to the formation of amorphous silica at 1300 °C, followed by cristobalite appeared by the crystallization of amorphous silica as the temperature was higher than 1400 °C. The sintering necks between ball-shaped Al2 O3 grains were formed by the pyrolyzed products of silicone resin. As the temperature was lower than 1500 °C, the phase composition consisted of Al2 O3 and silica. However, at 1600 °C, new mullite phases were in situ formed on the surface of ball-shaped Al2 O3 particles. The increasing silicone resin content promoted the formation of more mullite phase. Al2 O3 -based ceramic cores prepared had well dimensional stability during sintering, and the linear shrinkage rate reached the minimum value of 0.23% in the ceramic cores with silicone resin content of 20 wt% at 1400 °C. The open porosities of Al2 O3 -based ceramic cores prepared were 24.2~30.0% and relative densities were 63.9~70.2%. The bending strength increased with the increase in the sintering temperature, and the maximum value was obtained in the ceramic cores with silicone resin content of 15 wt% at the same sintering temperature. In our research, the highest bending strength reached to 77.06 MPa in the ceramic cores with silicone resin content of 15 wt% at 1500 °C.